Case Report: Prolonged VV-ECMO (111 Days) Support in a Patient With Severe COVID-19 - Xu, Zhiheng; Xu, Yonghao; Liu, Dongdong; Liu, Xuesong; Zhou, Liang; Huang, Yongbo; Li, Yimin; Liu, Xiaoqing (Frontiers in Medicine, 2021)
Venovenous extracorporeal membrane oxygenation (VV-ECMO) may be a lifesaving rescue therapy for patients with severe coronavirus disease 2019 (COVID-19). However, little is known regarding the efficacy of prolonged ECMO (duration longer than 14 days) in patients with COVID-19. In this case report, we report the successful use of prolonged VV-ECMO (111 days) in a 61-year-old man with severe COVID-19. Given the high mortality rate of severe COVID-19, this case provided evidence for use of prolonged VV-ECMO as supportive care in patients with severe COVID-19.